Highly thermal conductivity and flame retardant flexible graphene/MXene paper based on an optimized interface and nacre laminated structure. (February 2021) - Liu, Yingchun; Wu, Kun; Lu, Maoping; Jiao, Enxiang; Zhang, Hangzhen; Shi, Jun; Lu, Mangeng
Highlights: Multifunctional and free-standing GM film was prepared by a facile strategy. An optimized interface was constructed to decrease interface thermal resistance. GM film showed high thermal conductivity, superior flexibility and fire safety. Abstract: Low thermal conductivity (TC) and poor flame retardancy of graphene oxide (GO) have limited its application in thermal management. Herein, a facile strategy is developed to fabricate flexible and free-standing graphene/MXene (GM) films by filtration of MXene and GO dispersions, followed by reduction and thermal welding. As results, interlamellar insertion of MXene into graphene has occurred and optimized interface was constructed between MXene and graphene. According to Y. Agari's semi-empirical model and modified Maxwell-Garnett effective medium approximation, demonstrating that an optimized interface between MXene and graphene is conducive to heat conduction, and reduces the interface scattering. In-plane TC thus reached to 26.49 Wm −1 K −1, and the thermal boundary resistance decreased to 8.81 × 10 −10 from 1.54 × 10 −8 m 2 KW −1 . GM films also present excellent flame retardancy (peak heat release is ~10 Wg −1 ) and it still maintained initial shape after combustion. Using as-prepared GM films as heat dissipation, we demonstrate its potential usefulness in electronic device-cooling applications.